Investigation of the Quasi-Binary Phase Diagram FLiNaK-NdF3 - Peter Mushnikov (MDPI AG, 2021)
The NdF3 solubility in molten eutectic FLiNaK, which is a conceivable medium for a molten salt reactor (MSR), was determined by the quasi-binary phase diagram FLiNaK-NdF3. The eutectic mixture FLiNaK was prepared by direct melting of components LiF, NaF and KF·HF. The acidic anhydrous salt (KF·HF) was used instead of the hygroscopic KF. The NdF3 was sintered by hydrofluorination of Nd2O3. The oxygen impurity in the prepared eutectic FLiNaK, determined by an oxygen analyzer LECO OH836, was 0.036 wt.%, whereas the NdF3 contained 0.04 wt.% of oxygen. A part of the FLiNaK-NdF3 quasi-binary phase diagram was obtained using two thermal analysis techniques: differential thermal analysis (DTA) and differential scanning calorimetry (DSC). The FLiNaK-NdF3 phase diagram in the region of 0–30 mol.% NdF3 contains one eutectic at 2 mol.% NdF3 and 450 °C and two peritectic points: 8 mol.% NdF3 at 500 °C and 22 mol.% NdF3 at 575 °C. The region of the FLiNaK-NdF3 phase diagram below the liquidus line is rather complicated due to the complex structure of the multicomponent system in its molten state, as in its solid state. The NdF3 solubility in FLiNaK is about 5 mol.% at 490 °C and 29 mol.% at 700 °C; this means that the process of the MA transmutation in the MSR can be carried out in molten FLiNaK with a content of actinides as high as 15–20 mol.% in the temperature range of 550–650 °C.